STATUS HARA MAKRO PRIMER TANAH DI LAHAN PERTANIAN KECAMATAN TABUNDUNG KABUPATEN SUMBA TIMUR - Marten Umbu Nganji; Uska Peku Jawang (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Agricultural land is land that can affect agricultural productivity. Land, which is part of land resources, is the main component in the production of agricultural commodities. In supporting the productivity of agricultural commodities, there must be sufficient nutrients in the soil. Tabundung sub-regency is a producer of food crops, livestock and fisheries. As the main producer in the agricultural sector, the production of agricultural crops is not proportional to the total area of harvested land, meaning that the productivity of agricultural crops is not optimal if it is based on harvested area. The study was conducted in Tarimbang Village, Proud Watu and Tapil Regency of Tabundung. The method used in this research was survey technique and soil sampling was carried out in a composite manner. Soil samples were analyzed at the Nusa Cendana University Laboratory, Kupang. Primary data analyzed were elements of nitrogen (N), phosphorus (P), potassium (K), organic carbon (C), cation exchange capacity (CEC), and pH. The results showed that the overall nutrient status of N, P, and K were in the medium, high and very high categories, but there were some sample points that were in the low category for macronutrients N and P. While the concentrations of organic C, CEC and pH were overall generally in pretty good condition. This condition indicates that the research area provides sufficient nutrients for plant cultivation during the growth and yield of plants, but improvements are needed to overcome macronutrient deficiencies in several observation locations.